2014
DOI: 10.1093/mnras/stu2376
|View full text |Cite
|
Sign up to set email alerts
|

Composite bulges: the coexistence of classical bulges and discy pseudo-bulges in S0 and spiral galaxies

Abstract: We study nine S0-Sb galaxies with (photometric) bulges consisting of two distinct components. The outer component is a flattened, kinematically cool, disklike structure: a "disky pseudobulge". Embedded inside is a rounder, kinematically hot spheroid: a "classical bulge". This indicates that pseudobulges and classical bulges are not mutually exclusive: some galaxies have both.The disky pseudobulges almost always have an exponential disk (scale lengths = 125-870 pc, mean ∼ 440 pc) with disk-related subcomponents… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
158
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(175 citation statements)
references
References 119 publications
14
158
3
Order By: Relevance
“…A similar offset can be seen in NGC 4371 (PA = 86 • for the outer disc and 92 • for the inner ellipticity peak associated with the nuclear ring), which suggests that the nuclear disc/ring in NGC 4371 is slightly elliptical as well. Erwin et al (2014) estimate a ND mass of 7.6 × 10 9 M⊙ for NGC 4371, or 17 per cent of its total stellar mass, comparable to, but smaller than, the mass fraction measured in the model at 10 Gyr. The size of the ND, as a fraction of the deprojected radius at which the bar ellipticity peaks, is 0.17.…”
Section: Comparison To Ngc 4371mentioning
confidence: 47%
See 2 more Smart Citations
“…A similar offset can be seen in NGC 4371 (PA = 86 • for the outer disc and 92 • for the inner ellipticity peak associated with the nuclear ring), which suggests that the nuclear disc/ring in NGC 4371 is slightly elliptical as well. Erwin et al (2014) estimate a ND mass of 7.6 × 10 9 M⊙ for NGC 4371, or 17 per cent of its total stellar mass, comparable to, but smaller than, the mass fraction measured in the model at 10 Gyr. The size of the ND, as a fraction of the deprojected radius at which the bar ellipticity peaks, is 0.17.…”
Section: Comparison To Ngc 4371mentioning
confidence: 47%
“…Further details concerning the NDs, including their relation to the central bulges, can be found in Erwin et al (2014). For each galaxy, we orient the simulation to match the galaxy as best as possible, first reproducing the (deprojected) position angle of the bar relative to the line of nodes and then inclining the simulation by the same angle as the galaxy.…”
Section: Photometric Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to directly compare this sample with the Fisher & Drory (2011) catalogue, as the latter contains only 11 galaxies with M⋆ > 10 10.5 M⊙, while the former does not allow for a finer classification between pseudo and classical bulges. It is thus worth stressing that in the following plots fE formally represents an upper limit for the fraction of Elliptical galaxies, as it is not possible to discriminate the relative contribution of disk instabilities and merger processes in the formation of a spheroid, but only its main shape (but see Erwin et al 2015 for recent progress on these issues). Nonetheless, a more detailed classification should have a limited impact on our conclusions, since we do not expect the formation of B/T > 0.7 objects to be driven by disk instabilities alone, although they might contribute to increase the mass of a merger-induced spheroid.…”
Section: Resultsmentioning
confidence: 99%
“…Many external galaxies have been found to host compound bulges. For instance, Méndez-Abreu et al (2014) found that ∼ 30% of their sample of face-on barred galaxies showed signs of multiple bulge components, while Erwin et al (2015) presented a sample of nine galaxies with composite bulges (see also Erwin et al 2003). Thus, composite bulges are not rare, and it is conceivable that the Milky Way has one too.…”
Section: Introductionmentioning
confidence: 99%